Physical and mechanical properties of aluminum matrix composites reinforced with copper powder via stir casting method - Kholis, Nur; Purnama, Yudhi; Nugroho, Agung; Purwanto, Helmy; Hawari, Rizal (Jurnal Polimesin, 2025)
The stir casting method is a widely used technique for producing metal matrix composites by incorporating reinforcement particles into molten metal. This study investigates the effect of copper (Cu) powder reinforcement on the microstructure and mechanical properties of aluminum matrix composites fabricated using the stir casting method. The base material consists of recycled aluminum from vehicle wheels, with copper added as a reinforcement to enhance the mechanical characteristics of the cast material. The casting process involved melting aluminum waste at 650°C, followed by the gradual addition of Cu powder in varying volume fractions (2.5%, 5%, and 7.5%) while stirring at a constant speed of 500 rpm for 5 minutes to ensure uniform distribution. The microstructural analysis was conducted using optical metallography, while tensile and hardness properties were evaluated using a Universal Testing Machine. The results indicate that the most uniform powder distribution was achieved at 5% Cu reinforcement, whereas the highest porosity was observed at 7.5% due to particle agglomeration. The highest hardness value (42.52 BHN) was observed at 2.5% Cu reinforcement, while the maximum tensile strength (111.7 MPa) was obtained at 5% Cu. However, an increase in Cu content beyond 5% led to a decline in mechanical properties due to increased porosity and reduced bonding efficiency. These findings highlight the importance of optimizing Cu content in aluminum matrix composites to balance mechanical strength and structural integrity.